Review of the Correlation of LAT1 With Diseases: Mechanism and Treatment - Zhang, Jingshun; Xu, Ying; Li, Dandan; Fu, Lulu; Zhang, Xueying; Bao, Yigang; Zheng, Lianwen (Frontiers in Chemistry, 2020)
LAT1/SLC7A5 is a member of the system L transporter family. The main role of the LAT1 protein is to transport specific amino acids through cell membranes to provide nutrients to cells and participate in several metabolic pathways. In recent years, many studies have shown that LAT1/SLC7A5 is related to cancer, obesity, diabetes, and other diseases. However, the specific mechanism underlying the influence of LAT1/SLC7A5 remains unclear. Through the increasing number of studies on LAT1/SLC7A5, we have obtained a preliminary understanding of the function of LAT1/SLC7A5 in diseases. These studies also provide a theoretical basis for finding treatments for LAT1/SLC7A5-related diseases, such as cancer. This review summarizes the function and mechanism of LAT1/SLC7A5 and the treatment of LAT1/SLC7A5-related diseases. Support for the development of novel and reliable disease treatments are expected to be provided.